Các phương án lấy mẫu kiểm tra kinh tế với ba quyết định - Tung, Nguyen Thanh (Journal of Computer Science and Cybernetics, 2018)
We discuss the problem of constructing cost-optimal attributes acceptance sampling plans with three decision criteria. Hald’s Bayesian approach is utilized for finding the optimal plans. Basic assumptions are - The production process is in control with respect to the prior distribution π(p) so that the prior distribution of lot quality is a mixed binomial. - The decisions which will be considered regarding the remainder of lot are acceptance screening and rejection. - The per item cost of inspection, acceptance, screening are linear functions of the process average. - The decision criterion used is minimum average cost.